2010
DOI: 10.1007/s12032-010-9700-3
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, placebo-controlled, randomized phase III trial of chemotherapy plus epigenetic therapy with hydralazine valproate for advanced cervical cancer. Preliminary results

Abstract: The reversing of epigenetic aberrations using the inhibitors of DNA methylation and histone deacetylases may have therapeutic value in cervical cancer. This is a randomized phase III, placebo-controlled study of hydralazine and valproate (HV) added to cisplatin topotecan in advanced cervical cancer. Patients received hydralazine at 182 mg for rapid, or 83 mg for slow acetylators, and valproate at 30 mg/kg, beginning a week before chemotherapy and continued until disease progression. Response, toxicity, and PFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 41 publications
0
69
0
3
Order By: Relevance
“…So far, the combination of hydralazine and valproate has shown efficacy against myelodysplastic syndrome and a number of solid tumors (39,(43)(44)(45)(46) however, whether their clinical usefulness rely on their effect upon key processes of cancer such as proliferation, and apoptosis or on their effect upon the immune response to tumor remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the combination of hydralazine and valproate has shown efficacy against myelodysplastic syndrome and a number of solid tumors (39,(43)(44)(45)(46) however, whether their clinical usefulness rely on their effect upon key processes of cancer such as proliferation, and apoptosis or on their effect upon the immune response to tumor remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with these compounds enjoyed significantly greater progression-free survival compared to those that received cisplatin topotecan and placebo alone. 110 …”
Section: Nonnucleoside Analogsmentioning
confidence: 99%
“…The progression-free survival in the epigenetics + cisplatin group was 10 months, compared with 6 months in the cisplatin + placebo group (p < 0.05), and there was a trend towards greater rates of overall survival, objective response, and stable disease in the epigenetics group [Coronel et al 2011]. In another gynecological malignancy, a phase II trial in 17 heavily pretreated and platinum-resistant ovarian cancer patients demonstrated resensitization to carboplatin after treatment with DAC [Matei et al 2012].…”
Section: Chemosensitizationmentioning
confidence: 99%